Google Classroom and Self-Regulated Learning among Indonesian EFL Students: A Sequential Explanatory Mixed-Methods Study - Nur Husnil Khatimah; Adi Isma; Dwi Adi Nugroho; Amrang Amrang; Nurul Imansari (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Muslim Maros, 2026)
Self-regulated learning (SRL) remains underexplored in relation to specific learning management platforms across different SRL dimensions, particularly in post-pandemic Indonesian higher education. This study investigated how Google Classroom (GC) supported SRL among fifth-semester EFL students enrolled in a Computer Assisted Language Learning (CALL) course at Universitas Sulawesi Barat, Indonesia. A sequential explanatory mixed-methods design was employed, with quantitative data gathered from 47 students via a validated 12-item Likert-scale questionnaire, followed by semi-structured group interviews with 33 students across 11 purposively selected groups of three. Survey results indicated a high overall mean (M = 3.90, SD = 0.80, α = .933) across six SRL dimensions, with Planning and Time Management perceived as most strongly supported (M = 4.14) and Social Learning as least supported (M = 3.63). Thematic analysis yielded four themes: deadline notifications as a primary regulatory trigger, flexible material access enabling autonomous learning, unstable internet connectivity as a structural barrier, and limited collaborative affordances within the platform. The findings indicate that students perceived GC as particularly useful for planning, time management, and self-monitoring, although its support for social learning and co-regulation remained limited. These results carry practical implications for CALL pedagogy, platform design, and digital infrastructure investment in comparable higher education contexts.